The analysis of pharmacokinetic and pharmacogenomic impact on gefitinib efficacy in advanced non-small cell lung cancer patients: results from a prospective cohort study - Ma, Yuxiang (Ann Transl Med, 2019)
BACKGROUND: The current study is aimed to examine the impact of pharmacokinetics and gene polymorphisms of enzymes involving in absorption, distribution, metabolism and excretion (ADME) on the efficacy of gefitinib in non-small cell lung cancer (NSCLC) patients. METHODS: Eligible patients with indication of gefitinib treatment were prospectively enrolled in this study. Two peripheral blood samples at baseline and before cycle 2 day 1 were collected for the detection of single nucleotide polymorphisms (SNPs) of drug ADME enzymes and trough drug concentration (C(trough)) at steady state. Thirteen SNPs were genotyped using the Sequenom Massarray system. C(trough) was determined by validated high-performance liquid chromatographic method with tandem mass spectrometric (LC-MS/MS). RESULTS: Fifty-eight NSCLC patients were enrolled in this study. The median of C(trough) was 175ng/mL (range from 47.8 to 470 ng/mL). The trough concentration was not associated with either objective response or progression free survival (PFS). C(trough) was significantly lower in CYP3A4 rs2242480 CC + CT genotype than in TT genotype (P=0.019) and in ABCG2 rs2231142 AA genotype than in AC + CC genotype (P=0.031). ABCB1 rs2032582 dominant model was significantly correlated with overall response rate (ORR) and patients with GG phenotype respond better than patients with GT + TT phenotypes (84.6% vs. 51.2%, P=0.032). ABCB1 rs10256836 recessive model was significantly correlated with PFS and patients with GG phenotype achieved longer PFS than patients with GC + CC phenotypes (17.40 vs. 10.33 months, P=0.040). CONCLUSIONS: The C(trough) of gefitinib was significantly different between CYP3A4 and ABCG2 genotypes, but not with the efficacy of gefitinib treatment. ABCB1 rs2032582 and rs10256836 polymorphisms were correlated treatment outcome. Polymorphisms analysis of ABCB1 could be a predictive biomarker for gefitinib treatment.